Investimento público setorial no Ceará : otimização de estratégias com análise insumo-produto - Furtado, Pedro Luiz Honorato (2025)
This study proposes a novel methodology to simulate and evaluate the vector-based reallocation of final demand in the state of Ceará, Brazil. Using the Regional Input-Output Matrix of Ceará (MIPR/CE), a total of 12,433 allocation scenarios were simulated, including both deterministic vectors and weighted linear combinations. Each scenario is assessed based on its impact on Gross Output and the degree of production concentration across sectors. To rank the most promising scenarios, an arbitrary utility function is introduced, penalizing excessive concentration while favoring aggregate efficiency. The results indicate that combined scenarios—by distributing stimulus across different sectors—reduce the risks associated with production concentration without compromising average Gross Output levels. The optimal vector arrangement yielded a return of R$1.41 per real invested and a total Gross Output of R$45.21, while maintaining low sectoral concentration. Although preliminary, the study provides a promising methodological foundation that may evolve and support decision-making processes within government institutions.